Imaging Pain Relief in Osteoarthritis (IPRO): protocol of a double-blind randomised controlled mechanistic study assessing pain relief and prediction of duloxetine treatment outcome - Reckziegel, Diane; Bailey, Helen; Cottam, William J.; Tench, Christopher R.; Mahajan, Ravi P.; Walsh, David A.; Knaggs, Roger; Auer, Dorothee P. (BMJ Publishing Group, 2017)
Introduction: Osteoarthritis (OA) pain is a major cause of long-term disability and chronic pain in the adult population. One in five patients does not receive satisfactory pain relief, which reflects the complexity of chronic pain and the current lack of understanding of mechanisms of chronic pain. Recently, duloxetine has demonstrated clinically relevant pain relief, but only in half of treated patients with OA. Here the aim is to investigate the neural mechanisms of pain relief and neural signatures that may predict treatment response to duloxetine in chronic knee OA pain. Methods and analysis: This is an ongoing single-centre randomised placebo-controlled mechanistic study (2:1 [placebo] allocation), using a multi-modal neuroimaging approach, together with psychophysiological [quantitative sensory testing], genetics and questionnaire assessments. Eighty-one subjects with chronic knee OA pain are planned to power for between group comparisons (placebo, duloxetine-responder, and duloxetine-non-responder). Participants have a baseline assessment and, following six weeks of duloxetine (30mg for two weeks, then 60mg for four weeks), a follow-up evaluation. Brain imaging is performed at 3T with blood-oxygen-level dependent functional magnetic resonance imaging at rest and during pin-prick nociceptive stimulation for main outcome assessment; arterial spin labelling and structural imaging (T1- weighted) for secondary outcome assessment. Questionnaires evaluate pain, negative affect, quality of sleep and cognition. Ethics and dissemination: The study has been approved by the East Midlands – Nottingham 2 research ethics committee (18/EM/0189) and is being carried out under the principles of the Declaration of Helsinki (64th, 2013) and Good Clinical Practice standards. Results will be disseminated in peer-reviewed journals and at scientific conferences.